GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Expanding insights into plant rhabdovirus diversity through the discovery of viruses representing 32 putative novel species - Marleen Botermans; P. P. M. de Koning; M. Westenberg; I. P. Adams; K. Ben Mansour; C. Chabi-Jesus; C. de Krom; A. M. Dullemans; R. Festus; A. R. Fowkes; A. Fox; J. Freitas-Astúa; et al. (Archives of Virology, 2026)
Plant-infecting rhabdoviruses (family Rhabdoviridae , subfamily Betarhabdovirinae ) include several viruses that cause important crop diseases and are subject to phytosanitary regulation. Despite their agricultural and ecological importance, the diversity of plant rhabdoviruses and their impact on plant health remain poorly understood. Here, we report 32 tentative novel species of plant-infecting rhabdoviruses, identified via high-throughput sequencing and spanning nine established genera. The virus sequences originated from diverse hosts and geographic regions, revealing extensive diversity within the family Rhabdoviridae . Several viruses were detected independently in the same host species across multiple countries, demonstrating the practical value of data sharing for confirming host associations and gaining insight into the geographic distribution of these viruses. Our study highlights the underexplored diversity of plant rhabdoviruses and demonstrates the value of coordinated, collaborative virus discovery. With HTS now widely accessible, the challenge has shifted from virus discovery to making sequence data and metadata publicly available, and to conducting the time-consuming biological characterization often deprioritized in favour of viruses with immediate phytosanitary relevance. As a result, many findings remain unreported, leaving valuable data dormant on servers. By sharing genomic data prior to publication, we present an efficient approach to accelerate virus reporting, enable comparative analyses and advance understanding of virus diversity. We hope this collaborative effort will encourage further exploration of plant viruses, including those from hosts without discernable symptoms, supporting virus biology, taxonomy, pest risk assessments, and plant health policies.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Challenges and Strategic Recommendations for Enhancing Quantification and Projection of Forest Carbon Dynamics - Holly L. Munro; Christopher W. Woodall; William R. L. Anderegg; Jeff W. Atkins; Colin M. Beier; Bronson P. Bullock; Kendall DeLyser; David D. Diaz; Bianca N.I. Eskelson; Margaret E. K. Evans; John D. Foppert; Bryan C. Foster; et al. (Journal of Forestry, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Measuring the social impact of City-region food system initiatives (CRFSIs): A systematic review of indicators and metrics - K. Specht; C. Iodice; F. Monticone; P. Tonini; M. Petruzzelli; L. Carotti; R. Fox-Kämper; S. Toboso-Chavero; F. Orsini; A. Samoggia; M. Vittuari (Sustainable Cities and Society, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

First report of carnation Italian ringspot virus in Gypsophila in the United Kingdom - G. Webster; L. Frew; R. Ward; A. R. Fowkes; A. Skelton; V. Harju; I. P. Adams; S. McGreig; H. Pufal; C. Conyers; A. Fox (Journal of Plant Pathology, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Cohesion and shear strength of compacted lunar and Martian regolith simulants - B. Dotson; D. Sanchez Valencia; C. Millwater; P. Easter; J. Long-Fox; D. Britt; P. Metzger (Icarus, 2024)

Validation of a molecular sex marker in three sturgeons from eastern North America - Nicholas M. Sard; Brian R. Kreiser; Richard M. Pendleton; Barbara A. Lubinski; Robin L. Johnson; Dewayne A. Fox; Joel P Van Eenennaam; Jason E. Kahn; Chris Hager; Amanda L. Higgs; David C. Kazyak (Conservation Genetics Resources, 2024)

Co-alteration Network Architecture of Major Depressive Disorder: A Multi-modal Neuroimaging Assessment of Large-scale Disease Effects - Jodie P. Gray; Jordi Manuello; Aaron F. Alexander-Bloch; Cassandra Leonardo; Crystal Franklin; Ki Sueng Choi; Franco Cauda; Tommaso Costa; John Blangero; David C. Glahn; Helen S. Mayberg; Peter T. Fox (Neuroinformatics, 2023)

Characteristics of extreme daily precipitation events over the Canadian Arctic - Mark C. Serreze; Jessica Voveris; Andrew P. Barrett; Shari Fox; Peter D. Blanken; Alex Crawford (International Journal of Climatology, 2022)
Given growing interest in extreme high‐latitude weather events, we use records from nine meteorological stations and atmospheric reanalysis data to examine extreme daily precipitation events (leading, 99th and 95th percentile) over Arctic Canada. Leading events span 90 mm at Cape Dyer, along the southeast coast of Baffin Island, to 26 mm at Sachs Harbour, on the southwest coast of Banks Island. The 95th percentiles range from 20 to 30% of leading event sizes. Extreme events are most common on or near the month of climatological peak precipitation. Contrasting with Eurasian continental sites having a July precipitation peak corresponding to the seasonal peak in precipitable water, seasonal cycles in precipitation and the frequency of extremes over Arctic Canada are more varied, reflecting marine influences. At Cape Dyer and Clyde River, mean precipitation and the frequency of extremes peak in October when the atmosphere is quickly cooling, promoting strong evaporation from Baffin Bay. At all stations, leading events involved snowfall and strong winds and were associated with cyclone passages (mostly of relatively strong storms). They also involved strong vapour fluxes, sometimes associated with atmospheric rivers or their remnants. The most unusual sequence of events identified here occurred at Clyde River, where the three largest recorded precipitation events occurred in April of 1977. Obtaining first‐hand accounts of this series of events has proven elusive. Identified links between extreme events and atmospheric rivers demonstrates the need to better understand how the characteristics of such features will change in the future.

Comparisons between sequenced and re-sequenced genomes of historical subterranean clover mottle virus isolates - John Fosu-Nyarko; Ian P. Adams; Michael G. K. Jones; Adrian Fox; Roger A. C. Jones (Journal of Plant Pathology, 2022)
We report comparisons between the complete genomic sequences of five historical Western Australian isolates of subterranean clover mottle virus (SCMoV) from 1989–2000, and an infectious clone of its 1989 isolate. Sanger Sequencing (SS) and High Throughput Sequencing (HTS), or both, were used to obtain these genomes. Four of the SCMoV isolates were sequenced by SS in 1999–2002, but re-sequenced again by HTS in 2020. The pairs of sequences obtained from these four isolates differed by only 18–59 nucleotides. This small difference resulted from the different sequencing methods, the < 1–5 years each isolate was host passaged before freeze-drying prior to HTS sequencing, or a combination of both. Since SCMoV has not been reported outside Australia, this similarity suggests the population sequenced represents the progeny of either an indigenous virus that spread from a native legume to subterranean clover after its introduction or a recent seed-borne incursion from elsewhere. The ORF1 was the most variable, and the phylogenetic tree constructed with ORF1s showed the isolates grouped according to their symptom severity in subterranean clover, indicating the probability that ORF1-encoded P1 protein is a symptom determinant. A satellite RNA was associated with all SCMoV genomes obtained by HTS but none derived by SS.

Forty-year-old beet ringspot virus isolate: tests for potato true seed transmission, genome sequencing, recombination analysis and phylogenetic placement - Roger A. C. Jones; Aimee R. Fowkes; Sam McGreig; Adrian Fox; Ian P. Adams (Journal of Plant Pathology, 2022)
Summary Beet ringspot virus (BRSV) isolate IF came from a 1980 bait test on a Scottish soil sample. Between 1982 and 1984, it was used to study possible BRSV seed transmission in potato ( Solanum tuberosum ). To encourage flowering, potato scions were graft-inoculated onto tomato plants and these grafted plants were inoculated with IF. Flowers on BRSV-infected potato shoots were self-pollinated and their seeds collected. BRSV was found readily in pollen from these potato flowers, but never detected in any seedlings that grew from their seeds. Thus, although BRSV was present in pollen, no evidence of potato true seed transmission was obtained. In 1985, IF was preserved by freeze-drying and kept thereafter in a historical virus isolate collection. In 2020, it was subjected to high throughput sequencing and a complete genomic sequence was obtained. No recombination was detected in the IF sequence but its RNA1 and RNA2 were major parents of three, and a minor parent of one, recombinant BRSV isolates, respectively. Phylogenetic analysis of the P1 and P2 components of the coat protein gene encoded on its RNA2 placed the isolate IF sequence within the BRSV lineage. However, too few other BRSV sequences from different countries were present to provide information on its geographical associations.

Influence of Rising Water Temperature on the Temperate Seagrass Species Eelgrass (Zostera marina L.) in the Northeast USA - Holly K. Plaisted; Erin C. Shields; Alyssa B. Novak; Christopher P. Peck; Forest Schenck; Jillian Carr; Paul A. Duffy; N. Tay Evans; Sophia E. Fox; Stephen M. Heck; Robbie Hudson; Trevor Mattera; et al. (Frontiers in Marine Science, 2022)
Sea surface temperature (SST) has increased worldwide since the beginning of the 20th century, a trend which is expected to continue. Changes in SST can have significant impacts on marine biota, including population-level shifts and alterations in community structure and diversity, and changes in the timing of ecosystem events. Seagrasses are a group of foundation species that grow in shallow coastal and estuarine systems, where they provide many ecosystem services. Eelgrass, Zostera marina L., is the dominant seagrass species in the Northeast United States of America (USA). Multiple factors have been cited for losses in this region, including light reduction, eutrophication, and physical disturbance. Warming has the potential to exacerbate seagrass loss. Here, we investigate regional changes in eelgrass presence and abundance in relation to local water temperature using monitoring data from eight sites in the Northeastern USA (New Hampshire to Maryland) where a consistent monitoring protocol, SeagrassNet, has been applied. We use a hurdle model consisting of a generalized additive mixed model (GAMM) with binomial and beta response distributions for modeling eelgrass presence and abundance, respectively, in relation to the local summer average water temperature. We show that summer water temperature one year prior to monitoring is a significant predictor of eelgrass presence, but not abundance, on a regional scale. Above average summer temperatures correspond to a decrease in probability of eelgrass presence (and increased probability of eelgrass absence) the following year. Cooler than average temperatures in the preceding year, down to approximately 0.5°C below the site average, are associated with the highest predicted probability of eelgrass presence. Our findings suggest vulnerability in eelgrass meadows of the Northeast USA and emphasize the value of unified approaches to seagrass monitoring, conservation and management at the seascape scale.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Azole‐resistant Aspergillus fumigatus is highly prevalent in the environment of Vietnam, with marked variability by land use type - Tra‐My N. Duong; Thanh‐Van Le; Khanh‐Linh H. Tran; Phuong‐Tuyen Nguyen; Bich‐Phuong T. Nguyen; Thu‐Anh Nguyen; Huong‐Lan P. Nguyen; Bich‐Ngoc T. Nguyen; Matthew C. Fisher; Johanna Rhodes; Guy Marks; Greg J. Fox; et al. (Environmental Microbiology, 2021)
Summary Azole‐resistant environmental Aspergillus fumigatus presents a threat to public health but the extent of this threat in Southeast Asia is poorly described. We conducted environmental surveillance in the Mekong Delta region of Vietnam, collecting air and ground samples across key land‐use types, and determined antifungal susceptibilities of Aspergillus section Fumigati (ASF) isolates and azole concentrations in soils. Of 119 ASF isolates, 55% were resistant (or non‐wild type) to itraconazole, 65% to posaconazole and 50% to voriconazole. Azole resistance was more frequent in A. fumigatus sensu stricto isolates (95%) than other ASF species (32%). Resistant isolates and agricultural azole residues were overrepresented in samples from cultivated land. cyp51A gene sequence analysis showed 38/56 resistant A. fumigatus sensu stricto isolates carried known resistance mutations, with TR 34 /L98H most frequent (34/38).

Evidence of diverse movement strategies and habitat use by white sharks, Carcharodon carcharias, off southern Australia - Russell Bradford; T. A. Patterson; P. J. Rogers; R. McAuley; S. Mountford; C. Huveneers; R. Robbins; A. Fox; B. D. Bruce (Marine Biology, 2020)
Large endothermic pelagic sharks are highly migratory and use habitats spanning a broad range of coastal, neritic and oceanic areas. This study aimed to resolve the current lack of information on the movements and habitat use of white sharks, Carcharodon carcharias , between shelf, slope and oceanic areas located off southwestern Australia. Movement behaviours, spatial distribution patterns and vertical habitat use of juvenile, sub-adult and adult white sharks ranging in size from 1.9 to 5.7 m total length were examined using 43 satellite tags deployed over 15 years. Pop-up satellite archival tags and satellite-linked radio tags collected 3663 days and > 109,900 km of tracking data over periods of up to 381 days. We demonstrated sex-based differences in movement and distribution patterns of male (21) and female (19) white sharks. Female dispersal was broader and extended further offshore than males, which largely remained in neritic and gulf habitats. Female white sharks experienced a narrower range of water temperatures ( F = 9.0–19.0 °C; M = 10.4–24.8 °C). Despite these subtle differences, both sexes showed an affinity to the Neptune Island Group and the shelf slope canyons of the eastern Great Australian Bight, which are productive and oceanographically complex regions that support known prey of white sharks. This study highlighted that the southern-western Australian population of white sharks use off-shelf habitat to a greater extent than previously identified. Findings have potential implications for: ecological risk assessments of fisheries that operate in these offshore habitats and for monitoring and managing marine protected areas.

Genomic sequence and host range studies reveal considerable variation within the species Arracacha virus B - Roger A. C. Jones; Adrian Fox; Neil Boonham; Ian P. Adams (Archives of Virology, 2019)

SEASTAR: A Mission to Study Ocean Submesoscale Dynamics and Small-Scale Atmosphere-Ocean Processes in Coastal, Shelf and Polar Seas - Christine Gommenginger; Bertrand Chapron; Andy Hogg; Christian Buckingham; Baylor Fox-Kemper; Leif Eriksson; Francois Soulat; Clément Ubelmann; Francisco Ocampo-Torres; Bruno Buongiorno Nardelli; David Griffin; Paco Lopez-Dekker; et al. (Frontiers in Marine Science, 2019)

Climate change in context: putting people first in the Arctic - Henry P. Huntington; Mark Carey; Charlene Apok; Bruce C. Forbes; Shari Fox; Lene K. Holm; Aitalina Ivanova; Jacob Jaypoody; George Noongwook; Florian Stammler (Regional Environmental Change, 2019)

Leveraging linkage evidence to identify low-frequency and rare variants on 16p13 associated with blood pressure using TOPMed whole genome sequencing data - Karen Y. He; Xiaoyin Li; Tanika N. Kelly; Jingjing Liang; Brian E. Cade; Themistocles L. Assimes; Lewis C. Becker; Amber L. Beitelshees; Adam P. Bress; Yen-Pei Christy Chang; Yii-Der Ida Chen; Paul S. de Vries; et al. (Human Genetics, 2019)

The Application of Pulsed Electromagnetic Fields (PEMFs) for Bone Fracture Repair: Past and Perspective Findings - C. Daish; R. Blanchard; K. Fox; P. Pivonka; E. Pirogova (Annals of Biomedical Engineering, 2018)

Staying in place during times of change in Arctic Alaska: the implications of attachment, alternatives, and buffering - Henry P. Huntington; Philip A. Loring; Glenna Gannon; Shari Fox Gearheard; S. Craig Gerlach; Lawrence C. Hamilton (Regional Environmental Change, 2018)

Mother–infant interactions and regional brain volumes in infancy: an MRI study - Vaheshta Sethna; Inês Pote; Siying Wang; Maria Gudbrandsen; Anna Blasi; Caroline McCusker; Eileen Daly; Emily Perry; Kerrie P. H. Adams; Maria Kuklisova-Murgasova; Paula Busuulwa; Sarah Lloyd-Fox; et al. (Brain Structure and Function, 2017)

Balancing ecosystem function, services and disservices resulting from expanding goose populations - Ralph Buij; Theodorus C. P. Melman; Maarten J. J. E. Loonen; Anthony D. Fox (Ambio, 2017)

The role of the right temporoparietal junction in attention and social interaction as revealed by ALE meta-analysis - S. C. Krall; C. Rottschy; E. Oberwelland; D. Bzdok; P. T. Fox; S. B. Eickhoff; G. R. Fink; K. Konrad (Brain Structure and Function, 2015)

Large multiethnic Candidate Gene Study for C-reactive protein levels: identification of a novel association at CD36 in African Americans - Jaclyn Ellis; Ethan M. Lange; Jin Li; Josee Dupuis; Jens Baumert; Jeremy D. Walston; Brendan J. Keating; Peter Durda; Ervin R. Fox; Cameron D. Palmer; Yan A. Meng; Taylor Young; et al. (Human Genetics, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Differentiated parietal connectivity of frontal regions for “what” and “where” memory - C. Rottschy; S. Caspers; C. Roski; K. Reetz; I. Dogan; J. B. Schulz; K. Zilles; A. R. Laird; P. T. Fox; S. B. Eickhoff (Brain Structure and Function, 2013)

cry1 and GPA1 signaling genetically interact in hook opening and anthocyanin synthesis in Arabidopsis - Ana R. Fox; Gabriela C. Soto; Alan M. Jones; Jorge J. Casal; Jorge P. Muschietti; María A. Mazzella (Plant Molecular Biology, 2012)

A comparison of two microbial detection methods used in aseptic processing of musculoskeletal allograft tissues - Jeremy A. Dennis; Octavio V. Martinez; David C. Landy; Theodore I. Malinin; Paul R. Morris; William P. Fox; Billy E. Buck; H. Thomas Temple (Cell and Tissue Banking, 2011)

Distributions, life‐history specialization, and phylogeny of the rain forest vertebrates in the Australian Wet Tropics - S. E. Williams; J. VanDerWal; J. Isaac; L. P. Shoo; C. Storlie; S. Fox; E. E. Bolitho; C. Moritz; C. J. Hoskin; Y. M. Williams (Ecology, 2010)
The purpose of this data set was to compile distributional, general life‐history characteristics and phylogenies for Australian tropical rain forest vertebrates to inform a wide range of comparative studies on the determinants of biodiversity patterns and to assess the impacts of global climate change. We provide three distinct data sets: (1) a table of species‐specific distributional and life‐history traits for 242 vertebrate species found in the rain forests of the Australian Wet Tropics; (2) species distribution maps (GIS raster files) for 202 of the species displaying both the realized and potential distributions; and (3) phylogenies for these species. These species represent 93 birds, 31 amphibians, 31 mammals (including one monotreme), and 47 reptiles. Where information exists, the distributional and life‐history data compiled here present information on: indices of environmental specialization (ENFA), habitat specialization, average body mass and size, sexual dimorphism, reproductive characteristics such as age at first reproduction, clutch/litter size, number of reproductive bouts per year and breeding seasonality, longevity, time of day when most active, and dispersal ability; distributional characteristics such as range size (potential and realized for both total and core ranges) and observed ranges in temperature, precipitation, and elevation; and niche attributes such as environmental marginality and specialization. The distribution maps provided represent a combination of presence‐only ecological niche modeling (using MaxEnt) to estimate the potential distribution of a species followed by biogeographic clipping by expert opinion based on extensive field data and a subregional classification relevant to the topography and biogeographic history of the region to produce best‐possible estimates of the realized distribution. Our assemblage contains many species with a shared evolutionary history, and thus many analyses of these data will need to account for phylogeny. Although a comprehensive phylogeny with branch length information does not exist for this diverse group of species, we present a best‐estimate composite phylogeny constructed primarily from recently published molecular phylogenies of included groups. The complete data sets corresponding to abstracts published in the Data Papers section of the journal are published electronically in Ecological Archives at 〈 http://esapubs.org/archive 〉. (The accession number for each Data Paper is given directly beneath the title.)

Positive Allosteric Interaction of Structurally Diverse T-Type Calcium Channel Antagonists - Victor N. Uebele; Cindy E. Nuss; Steven V. Fox; Susan L. Garson; Razvan Cristescu; Scott M. Doran; Richard L. Kraus; Vincent P. Santarelli; Yuxing Li; James C. Barrow; Zhi-Qiang Yang; Kelly-Ann S. Schlegel; et al. (Cell Biochemistry and Biophysics, 2009)

Nitrogen Phytoremediation by Water Hyacinth (Eichhornia crassipes (Mart.) Solms) - L. J. Fox; P. C. Struik; B. L. Appleton; J. H. Rule (Water, Air, & Soil Pollution, 2008)

Is fecundity in plaice ( Pleuronectes platessa L.) down‐regulated in response to reduced food intake during autumn? - J. Kennedy; P. R. Witthames; R. D. M. Nash; C. J. Fox (Journal of Fish Biology, 2008)
The effect of controlling food intake during the autumn, which is the time of late vitellogenesis, on fecundity, atresia and follicle and ovary growth was examined for plaice Pleuronectes platessa . Eighteen fish were kept in individual pens and either fed on a high or low ration diet. Fish which increased in whole body condition exhibited an increase in carcass condition which means that when food intake is sufficient to maintain whole body condition some resources are used as storage. Follicle growth rate was positively correlated with change in Fulton’s condition and total atresia was negatively correlated with change in Fulton’s condition. Thus, the rate of vitellogenesis was dependent on the availability of an exogenous food source. Fecundity at the end of the experiment was positively correlated with mass and total length. Food intake had no effect on relative fecundity; however, fish which had a lower food intake lost mass and had a greater intensity of atresia, lowering their absolute fecundity. One fish in a very low condition at the start of the experiment skipped spawning and one fish exhibited a decrease in average follicle diameter during the experiment which is hypothesized to be a prelude to mass atresia.

NeuroAIDS, Drug Abuse, and Inflammation: Building Collaborative Research Activities - Joan W. Berman; Monica J. Carson; Linda Chang; Brian M. Cox; Howard S. Fox; R. Gilberto Gonzalez; Glen R. Hanson; Kurt F. Hauser; Wen-Zhe Ho; Jau-Shyong Hong; Eugene O. Major; William F. Maragos; et al. (Journal of Neuroimmune Pharmacology, 2006)

The importance of individual behaviour for successful settlement of juvenile plaice ( Pleuronectes platessa L.): a modelling and field study in the eastern Irish Sea - C. J. FOX; P. MCCLOGHRIE; E. F. YOUNG; R. D. M. NASH (Fisheries Oceanography, 2006)
To study the transport of plaice ( Pleuronectes platessa L.) eggs and larvae in the eastern Irish Sea, we constructed a 3D‐baroclinic physical model and coupled it to a particle‐tracking scheme that allowed aspects of larval behaviour to be simulated. Starting positions for eggs were based upon data from a series of ichthyoplankton surveys and final positions were compared with results of settled plaice distributions from two beam trawl surveys conducted on beaches around the eastern Irish Sea. If simulated larval behaviour was limited to passive drift or horizontal swimming, the particles diffused away from the spawning areas but failed to reach nursery grounds in significant numbers (85–90% remaining offshore). In contrast, switching on circatidal vertical swimming significantly increased the numbers of larvae reaching the coast (only 23–30% remained offshore). Particles tended to accumulate in bays and estuaries and this pattern compared well with the distribution of settled plaice from the field surveys. Studies in the southern North Sea (where spawning and nursery grounds are widely separated) have also demonstrated the importance of selective tidal stream transport for successful recruitment of settling plaice to nursery grounds. Although our understanding of the ontogeny of this behaviour is still poor, the model results presented suggest that this aspect of behaviour is a key factor influencing plaice settlement success.

Prey size selection and distance estimation in foraging adult dragonflies - R. M. Olberg; A. H. Worthington; J. L. Fox; C. E. Bessette; M. P. Loosemore (Journal of Comparative Physiology A, 2005)

Retinal and extraocular cytomegalovirus end-organ disease in HIV-infected patients in Europe: a EuroSIDA study, 1994?2001 - I. Yust; Z. Fox; M. Burke; A. Johnson; D. Turner; A. Mocroft; C. Katlama; B. Ledergerber; P. Reiss; O. Kirk (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Glycoconjugates in the otolithic membrane of herring larvae: a possible framework for encoding the life history recorder in fishes - P. Tytler; C. J. Fox; A. Folkvord (Journal of Fish Biology, 2002)
Glycoconjugates in the inner ear of herring Clupea harengus larvae, investigated by laser confocal and electron microscopy, were located mainly in the gelatinous layer of the otolithic membranes, forming a collar around the proximal surfaces of the otoliths. The site of secretion was located on the surface of the sensory macula, from which a colonnade of glycoconjugate streamers projected through the subcupular region to connect with the gelatinous layer of each otolith. An electron dense component of the outer gelatinous layers, shown by TEM to be closely associated with the sensory kinocilia, suggested that they provided a basis for the streamers and offered a potential role in directing the path of secretion. It is hypothesized that this highly structured glycoconjugate framework could provide a mechanism for localizing and containing ionic and protein gradients previously detected in this vicinity and which are considered to have a key role in driving the differential growth and mineralization of the otoliths.

Morphological variation of the saker (Falco cherrug) and the implications for conservation - Chris P. Eastham; Mike K. Nicholls; Nick C. Fox (Biodiversity and Conservation, 2002)

The April 1992 Cape Mendocino Earthquake Sequence: Seismo-Acoustic Analysis Utilizing Fixed Hydrophone Arrays - R. P. Dziak; C. G. Fox; H. Matsumoto; A. E. Schreiner (Marine Geophysical Research, 1997)

Acceleration of cheese ripening - P. F. Fox; J. M. Wallace; S. Morgan; C. M. Lynch; E. J. Niland; J. Tobin (Antonie van Leeuwenhoek, 1996)

Synergistic effects of Aroclor 1254 and mirex on the semen characteristics of American Kestrels - D. M. Bird; P. H. Tucker; Glen A. Fox; P. C. Lagu (Archives of Environmental Contamination and Toxicology, 1983)